Efficacy and safety of pricking-blood therapy for acute gouty arthritis: A protocol for systematic review and meta-analysis. Issue 50 (11th December 2020) - Li, Renliang; Zhang, Ping; Hu, Ziyi; Yi, Ying; Chen, Lisha; Zhang, Hengyi; Li, Hong; Liu, Wanting; Wu, Mengwen
Abstract: Background: Acute gouty arthritis is a joint inflammatory reaction that affects the daily quality of patients. Previous reviews of pricking-blood therapy for acute gouty arthritis have been growing, but a systematic review is not available. This study aimed to systematically investigate the efficacy and safety of pricking-blood therapy in treating acute gout arthritis. Methods: We will search for relevant literature through Chinese and English databases, with the retrieval deadline being December 2020. Databases include PubMed, Embase, Web of Science, the Cochrane Library, China National Knowledge Infrastructure, the Chongqing VIP Chinese Science and Technology Periodical Database, Wanfang Database, and China Biomedical Literature Database. We will also manually search Chinese Acupuncture & Moxibustion, Acupuncture Research, Chinese Clinical Trial Register, and unpublished studies or references. According to the inclusion and exclusion criteria, the literature will be screened, and the data are extracted independently by the 2 researchers. The primary outcomes were the total effective rate and Visual Analogue Scale (VAS) score. RevMan 5.3.5. software will be used for statistical analysis. According to the Grades of Recommendation, Assessment, Development, and Evaluation (GRADE), each evidence of outcome quality will be appraised. Results: This study will provide a comprehensive review of current evidence for a pricking-blood therapy treatment for acute gouty arthritis. Conclusion: The efficacy and safety of picking-blood therapy in treating acute gout arthritis will be evaluated. Unique INPLASY number: INPLASY2020100094.